2020
DOI: 10.1177/0018726720908649
|View full text |Cite
|
Sign up to set email alerts
|

We have emotions but can’t show them! Authoritarian leadership, emotion suppression climate, and team performance

Abstract: How do authoritarian leaders in modern organizations influence work team emotional climate and performance? Defining authoritarian leadership as an ambient, demanding, and controlling leadership style, we conducted a survey study of 252 leaders and 765 subordinates matched in 227 work teams in three large public Japanese organizations. The results indicate that authoritarian leaders are more likely to create a team climate of emotion suppression, which induces a higher level of team emotional exhaustion that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 116 publications
1
70
0
2
Order By: Relevance
“…Paternalistic leadership has a favorable impact on employee attitudes in high-power-distant societies ( Schaubroeck et al, 2017 ). In a high-power-distant culture, leaders adopt an authoritative approach that results in improved performance ( Wang and Guan, 2018 ; Chiang et al, 2021 ). Sue-Chan and Ong (2002) discussed that individuals of high-power-distant cultures find assigned goals effective in increasing their self-efficacy beliefs because they believe that assigned goals are communicated from an authoritative source.…”
Section: Introductionmentioning
confidence: 99%
“…Paternalistic leadership has a favorable impact on employee attitudes in high-power-distant societies ( Schaubroeck et al, 2017 ). In a high-power-distant culture, leaders adopt an authoritative approach that results in improved performance ( Wang and Guan, 2018 ; Chiang et al, 2021 ). Sue-Chan and Ong (2002) discussed that individuals of high-power-distant cultures find assigned goals effective in increasing their self-efficacy beliefs because they believe that assigned goals are communicated from an authoritative source.…”
Section: Introductionmentioning
confidence: 99%
“…Second, our study findings highlight the role of person–supervisor fit in motivating prohibitive voice. Authoritarian leadership generally emphasizes employees’ unconditional obedience ( Farh and Cheng, 2000 ) and is less open to their ideas—attitudes that evoke employees’ emotional fear ( Wu et al, 2002 ) and team emotional exhaustion ( Chiang et al, 2021 ). These side effects are likely to have an especially strong influence on less political skilled employees because they lack the capacity to address psychological uncertainty and unsafety at work.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Chiang, Chen, Liu, Akutsu, and Wang (2021) found that authoritarian leadership was associated with a team affective climate of suppression (particularly when the leaders themselves suppressed emotion), which in turn was associated with team emotional exhaustion and low performance, and Menges and Kilduff (2015) argue that leaders who suppress the expression of negative affect may foster an affective climate of fear, anger, and mistrust.…”
Section: Leadershipmentioning
confidence: 99%